Scientific and pedagogical principles of personality-oriented technologies of music education of junior schoolchildren (Pedagogy of Higher and Secondary Education, 2011)
In the articles exposed scientifically pedagogical principles of the personality orientated technologies of musical of junior schoolboys. Specific principles of this type of are.
Keywords: musical junior schoolboys; personality orientated technologies